(untitled) (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2021)
Seismic data always consists of the desired main signal and a noise component. Therefore, this study aims to reduce coherent and random noise in data by using different methods in order to increase the resolution of the data so that the interpretation of the data becomes accurate. Random noise can be removed easily by bandpass filtering and stacking with significant results while coherent noise has to go through more complex stages because coherent noise can overlap with data. Aru waters, where the data for this study was taken, is geographically located at the meeting point of 3 large active plates so that it has great potential in the oil and gas sector. This study uses two main methods to attenuate coherent noise to see the different results of the methods applied to data. The coherent filter which target swell noise and coherent denoising method which target linear coherent noise both produces satisfactory final results. These methods successfully attenuated main target noise that associated with both methods, but coherent denoising method still leaves a faint trace of swell noise inside cross section on the final result. The coherent filter method and the coherent denoising method are quite effective in identifying and attenuating random and coherent noise in the data, but the difference between the two methods lies in the noise target that can be attenuated maximally.